The Correlation between Academic Ability and Scientific Skills in The Selection of Outstanding School Library Staff - Rismita, Rismita (Journal of Education Reseach and Evaluation, 2020)
Selection of outstanding school librarians due to increased information literacy has an impact on student achievement but in the implementation of the scientific skills assessment some participants do not understand the testing standards and have difficulty interpreting the principles of the measured test. The research objective was to examine the relationship between academic ability and scientific skills. Respondents amounted to 35 school library staff using purposive sampling. Validity and reliability were analyzed from the highest assessment of each level of education based on the top three rankings using the Spearman rank correlation. The results showed a significant relationship between academic ability and scientific skills of outstanding school library staff with ρ value = 0.784 and ρ table at α = 5% was 0.683. That is, high academic ability results in an increase in the scientific skills of outstanding school librarians. This research has implications for maintaining the professional balance of library personnel who are integrated with technological developments that have a positive impact on schools in dealing with the transition to electronic-based systems.